2018
DOI: 10.1021/acscombsci.7b00135
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic Structure Analysis of a Ti–Ta Thin Film Materials Library Fabricated by Combinatorial Magnetron Sputtering

Abstract: Ti-Ta thin films exhibit properties that are of interest for applications as microactuators and as biomedical implants. A Ti-Ta thin film materials library was deposited at T = 25 °C by magnetron sputtering employing the combinatorial approach, which led to a compositional range of TiTa to TiTa. Subsequent high-throughput characterization methods permitted a quick and comprehensive study of the crystallographic, microstructural, and morphological properties, which strongly depend on the chemical composition. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 69 publications
(153 reference statements)
2
9
0
Order By: Relevance
“…3.260 3.295 [11], 3.286 [14] 3.278 [24], 3.274 [25] A series of structural optimizations are performed on the crystal structure of the Ti0.5Ta0.5 alloy under different applied pressures to get the corresponding volumes and equilibrium lattice constants, which are used to investigate the impacts of applied pressure on the unit cell volume and lattice constant. Subsequently, the dependencies of dimensionless ratios 0 V V and 0 a a on the applied pressure are obtained in the range of −10 to 50 GPa, where the negative pressure denotes the tension, as shown in Figure 3.…”
Section: Ti05ta05 Alloymentioning
confidence: 99%
See 2 more Smart Citations
“…3.260 3.295 [11], 3.286 [14] 3.278 [24], 3.274 [25] A series of structural optimizations are performed on the crystal structure of the Ti0.5Ta0.5 alloy under different applied pressures to get the corresponding volumes and equilibrium lattice constants, which are used to investigate the impacts of applied pressure on the unit cell volume and lattice constant. Subsequently, the dependencies of dimensionless ratios 0 V V and 0 a a on the applied pressure are obtained in the range of −10 to 50 GPa, where the negative pressure denotes the tension, as shown in Figure 3.…”
Section: Ti05ta05 Alloymentioning
confidence: 99%
“…From the variation curves, it can be found that the two ratios decrease when applied pressure increases and the descent speed for 0 V V is significantly faster compared to 0 a a , suggesting that applying pressure can greatly reduce interatomic distance, and then strengthen electron interactions between adjacent atoms in the Ti0.5Ta0.5 alloy. Lattice constant a 0 (Å) 3.260 3.295 [11], 3.286 [14] 3.278 [24], 3.274 [25] A series of structural optimizations are performed on the crystal structure of the Ti 0.5 Ta 0.5 alloy under different applied pressures to get the corresponding volumes and equilibrium lattice constants, which are used to investigate the impacts of applied pressure on the unit cell volume and lattice constant. Subsequently, the dependencies of dimensionless ratios V/V 0 and a/a 0 on the applied pressure are obtained in the range of −10 to 50 GPa, where the negative pressure denotes the tension, as shown in Figure 3.…”
Section: Ti05ta05 Alloymentioning
confidence: 99%
See 1 more Smart Citation
“…A possible alternative to Ni-Ti as high-temperature shape memory alloys (HTSMAs) 14,15 are Ti-Ta alloys [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] . In these alloys, the transformation temperatures A s and M s increase with decreasing Ta concentration c Ta , and can be as high as 430 • C when c Ta is reduced to 20 at.% 30 .…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations we have employed ab initio molecular dynamics (aiMD) simulations to access structural properties at finite temperature, and combined our ab initio data with a 2-4-6 Landau-Falk expansion of the free energy [12,13] to characterize the nature of reversible MTs and suggest necessary conditions to distinguish them from irreversible ones. We have applied our method to the shape memory alloy Ti-Ta [14][15][16][17][18][19][20][21][22][23] that features a reversible MT with a high (>100 • C) transition temperature. Our key findings include that, in this system, there is only a small interval of temperatures where austenite and martensite are both dynamically stable and that, in this interval, the two phases are separated by an extremely small free energy barrier.…”
mentioning
confidence: 99%